Konstruksi Pemikiran Madzhab Asy’ari dalam Tafsir Jalalain - Faqih, Muhammad Ikhsanul (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
Tafsir Jalalain is one of the most widely studied commentaries in Indonesia. This commentary was written by two commentators, namely Jalaluddin al-Mahalli and Jalaluddin as-Suyuthi. Both are adherents of the Ash'ariyah school of thought in terms of theological thinking. So that in interpreting the verses related to faith, both tend to follow what is taught by the Asy'ariyah school. This can be seen in several verses relating to the main discussion in the Asy'ariyah teachings as well as in the mutasayabihat verses, the verses about seeing Allah, the verses about the position of people who commit major sins and other verses related to them. In these verses, these two commentators provide explanations that are not much different from what is taught by the Asy'ariyah school. Of course with a concise and global explanation.